2x/7 = 12/14
Multiply both sides of the equation by 7:
2x = 84/14
Simplify:
2x = 6
Divide both sides by 2 and your answer is....
x = 3
Answer:
1. is no
Step-by-step explanation:
.
Answer:
Point P = (-9,11)
Step-by-step explanation:
Point M: (1,3) X and Y have the 2 on the bottom right of them
Midpoint N: (-5,7)
Point P: (X*2, Y*2)
( 1 + X*2 3 + Y*2 )
( _______ ________ ) = (-5 , 7)
( 2 , 2 )
( 1 + X*2 )
( _____ ) = -5
( 2 )
Then multiply the left equation above by 2, and that cancels out the 2 being
divided on the bottom. Also, multiply the -5 by 2 and you get -10
1 + X*2 = -10
+1 +1
__________
X*2 = -9
X = -9
( 3 + Y*2 )
( ______ ) = 7
( 2 )
Then multiply the left equation above by 2, and that cancels out the 2 being divided on the bottom. Also, multiply the 7 by 2 and you get 14
3 + Y*2 = 14
-3 -3
_________
Y*2 = 11
Y = 11
Hope this helps, good luck! :)
Answer:
0
Step-by-step explanation:
Plug in 11 for m. Remember to follow PEMDAS. First solve the parenthesis, then multiply.
m = 11
7(m - 11) = 7(11 - 11) = 7(0) = 0
0 is your answer.
~
Answer:
90 90909090909090909090909090